Rationale for targeting complement in COVID‐19. Issue 8 (12th July 2020) - Polycarpou, Anastasia; Howard, Mark; Farrar, Conrad A; Greenlaw, Roseanna; Fanelli, Giorgia; Wallis, Russell; Klavinskis, Linda S; Sacks, Steven
Abstract: A novel coronavirus, SARS‐CoV‐2, has recently emerged in China and spread internationally, posing a health emergency to the global community. COVID‐19 caused by SARS‐CoV‐2 is associated with an acute respiratory illness that varies from mild to the life‐threatening acute respiratory distress syndrome (ARDS). The complement system is part of the innate immune arsenal against pathogens, in which many viruses can evade or employ to mediate cell entry. The immunopathology and acute lung injury orchestrated through the influx of pro‐inflammatory macrophages and neutrophils can be directly activated by complement components to prime an overzealous cytokine storm. The manifestations of severe COVID‐19 such as the ARDS, sepsis and multiorgan failure have an established relationship with activation of the complement cascade. We have collected evidence from all the current studies we are aware of on SARS‐CoV‐2 immunopathogenesis and the preceding literature on SARS‐CoV‐1 and MERS‐CoV infection linking severe COVID‐19 disease directly with dysfunction of the complement pathways. This information lends support for a therapeutic anti‐inflammatory strategy against complement, where a number of clinically ready potential therapeutic agents are available. Abstract : This review offers a balanced view on how the complement system may be engaged in COVID‐19 and suggests therapeutic strategies, some of which already in clinical trials.